Security, Identity, and British Counterterrorism Policy - Fisher, Kathryn Marie. author. aut Link
XV, 270 p.
Keywords: Counterterrorism laws and policies have become a normalized fixture of security agendas across the globe. How do 'us/them' identity constructions contribute to the legitimizing strategies surrounding this development? The British case provides a historically-situated illustration which is of ongoing significance for security and insecurity today.